"The farm that became a great problem": Epworth Mission Station and the manifestation of mission in crisis in post-independence Zimbabwe - Ncube, Richman; Kgatla, Selaelo Thias ca. 20./21. Jh. (2021)
Mission stations were created to radiate the light of Christianity to the surrounding communities. However, as time passed, what was meant to be the light became an eyesore to the noble intentions of the initial founders. Epworth Mission Station brings together the manifestation of a failed mission vision, as exemplified by the challenges and the squalid conditions of what was once a promising mission. This study explores the origins and challenges faced at a mission station and in particular Epworth of the Methodist Church in Harare. It looks at the challenges of the 19th-century mission approach in a post-colonial era. With the changes in political and religious terrain in Africa, mission work has suffered.Contribution: Using qualitative methods, which included desk research, archival and ethnographic approaches, the researcher sought to uncover the latent sources and nature of the mission problems and ended by suggesting what new approaches can be used to salvage respectability of mission in a post-colonial era. These include missional orientation and decolonisation of the African mind.
Keywords: Methodist; Epworth; Missional Orientation; Decolonisation; Missional Ecclesiology; Paradigm Shift; Mission Station